Genotype dependant variation in arbuscular mycorrhizal colonization of tobacco (Nicotiana tabacum) - SUBHASHINI, D V; MURTHY, T G K (The Indian Journal of Agricultural Sciences, 2025)
Arbuscular mycorrhizal (AM) fungi (Phylum Glomeromycota) form ubiquitous symbiosis with most terrestrial plants by fungal species belonging to genera Glomus, Entrophospora, Acaulospora, Gigaspora, Scutellospora, Archaeospora and Paraglomus. These fungi impart many benefits to plants. Colonization of roots by AM fungi has been shown to improve growth and productivity of several field crops by increasing nutrient element uptake (Subhashini and Padmaja 2010). These fungi are also known to enhance crop growth and yield through enhanced tolerance to various biotic and abiotic stress factors and improving physical, chemical and fungi are also known to enhance crop growth and yield through enhanced tolerance to various biotic and abiotic stress factors and improving physical, chemical and biological properties of soil (Riedel et al. 2008). Research in the past years has proved that AM fungi can improve plant growth through increased uptake of phosphorus and other mineral nutrients, especially in low fertile soils (Hamel and Strullu 2006). In general, AM fungi improve the P uptake of their host plant especially under P limited conditions (Mohammed et al. 2004). AM fungi explore the soil more thoroughly and hence are able to locate and use the point source of P (Subhashini 2013b). The incidence of AM in tobacco has already been reported (Subhashini and Padmaja 2012). Based on the earlier reports that AM inoculation can increase the recovery of phosphatic fertilizer from soil by plants, field experiment was conducted at CTRI, Rajahmundry to find out the incidence of AM colonization and spore density in tobacco (Nicotiana tabacum L.) genotypes grown in vertisols. The present study is aimed to know whether the variation in AM symbiosis in tobacco crop is genotype dependant.